Hubungan Pelayanan Antenatal Care Dengan Kejadian Stunting Pada Anak Usia 24-59 Bulan Di Puskesmas Kotabunan Kecamatan Kotabunan - Madi, Anita Sovia; Babakal, Abram; Simanjuntak , Susi Roida (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background: Stunting is a nutritional problem caused by lack of nutritional intake starting from the process of pregnancy so that children fail to achieve physical development measured by height according to age (TB / U). The prevalence of stunting children in the Kotabunan Health Center is still high, which is 8.99% of 385 children with stunting. One of the indirect factors causing stunting in children is antenatal care services carried out by mothers. Objective: this study aims to determine how the relationship between antenatal care services and the incidence of stunting in children aged 24-59 months at the Kotabunan Health Center. Method: this study is a quantitative research with a cross sectional study design using a retrospective approach. The sampling technique used is total sampling based on stunting incident reports from the Kotabunan Health Center. Data collection tools in the form of 10T questionnaires, antenatal care services, and MCH books. Discussion: most of the respondents of mothers with stunting children at the Kotabunan Health Center have made antenatal care visits >4 times and have carried out antenatal care services according to standards. Conclusion: In the study, there was no relationship between antenatal care services and the incidence of stunting where antenatal care services are one of the indirect factors causing stunting.